Glycogen resynthesis rate following cross-country skiing is closely correlated to skeletal muscle glycogen content - Ortenblad, N.; Nielsen, J.; Saltin, B.; Holmberg, H. C. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: In skeletal muscle, glucose is stored as glycogen, which is a major source of energy during most forms of muscle activity. It is now well recognized that muscle glycogen stores are closely related to performance and endurance capacity. Thus, successful competition or training depends on an optimal glycogen resynthesis rate before a subsequent exercise session. The purpose of the present study was to evaluate the glycogen resynthesis rate in elite cross-country (cc) skiers, following exhaustive exercise, and to examine the role of muscular glycogen content on the resynthesis rate.